Amputation of the first metatarsophalangeal joint due to a giant gouty tophi: A case report. Issue 43 (October 2017) - Zhou, Chenchen; Xue, Cheng; Yang, Bo; Wang, Wutao; Xu, Yanqiu; Huang, Fang; Wang, Yi
Abstract: Rationale: The first metatarsophalangeal joint (MTP1) is the most frequent site of gouty tophi. We report an unusual case with a giant skin-perforating tophi. This is the first case of gouty tophi at MTP1 which accepts surgical debulking and amputation. Patient Concerns: A 42-year-old man presented with a seven-year history of gout and a giant tophi at MTP1. The patient was referred to hospital due to persistent pain and ulcerations on the surface of the left MTP1. This rounded, giant, swelling, tophaceous tophi severely interfered with his normal walking. Diagnoses: The patient was diagnosed with gouty arthritis seven years ago, and did not receive regular anti-gout treatments. Outcomes: Biochemical examination showed he had raised serum uric acid (SUA, 11.92 mg/dl) and creatinine (258 μmol/l). There was a severe joint destruction of MTP1 by X-ray examination. We controlled the skin infection by sulbenicillin. He was given febuxostat to reduce SUA. After 3 months of treatment, SUA fell to 6.8 mg/dl. Then we performed surgical debulking of MTP1 and amputation of hallux. Surgical operations obviously relieved the pain, and improved the function of his left foot. The visual closure after amputation was good. Conclusion: Surgical amputation of the gout lesion at MTP1 maximized the function, and reduced the pain of this patient. In the case of giant tophi with severe gouty arthritis or skin infections, surgical decisions need to weigh gains and losses carefully.